The impact of mental training program to advance shooting performance level of basketball juniors - Kassem Shalaby, H. (World Journal of Sport Sciences, 2010)
The aim of this study was to identify the effectiveness of a mental training program on improving the shooting level of basketball beginners. A sample of 30 players of age under 16 years old of Young Muslims Club in Port Said has been selected (15.404±0.794 years and 4.313±0.769 years). They have been divided into two groups (experimental and control). The experimental group was subjected to a mental training program of eight weeks at five units of training each week at a rate of 15 to 30 minutes. The most important results have indicated to remarkable progress in the various research variables: the perception of time and distance, the ability to relax, performance level, visual spatial perception and the percentage of shooting while there was no significant progress compared to what is achieved when the mental training program preceded the implementation of the sports training program.